PP.14.14: GERANIOL AND 10-GINGEROL RESTORE NORMAL VASCULAR REACTIVITY IN AORTA ISOLATED FROM DIABETIC RATS. (June 2015) - El-Bassossy, H.; Ghareib, S.; Elberry, A.; Azhar, A.; Banjar, Z.; Watson, M.
Abstract : Objective: Alterations in vascular reactivity play important roles in diabetic vascular complications which, in turn, can develop into further serious complications. Geraniol and 10-gingerol are two ginger ingredients with reported anti-inflammatory and antioxidant activities. The present work investigates the effect of geraniol and 10-gingerol on the changes in vascular reactivity associated with diabetes. Design and method: Diabetes was induced in rats by single intraperitoneal injection of streptozotocin (50 mg.kg-1). Animals were left for 8 weeks after streptozotocin injection to develop vascular complications. Then, rings of rat isolated thoracic aorta were used to measure the vasoconstrictor responses to cumulative concentrations of phenylephrine (PE) and the relaxation responses to the endothelial dependent relaxant acetylcholine (ACh). Results: Streptozotocin injection induced moderate hyperglycemia that lasts for 8 weeks. Aortic rings isolated from diabetic animals (C) showed exaggerated contractility responses to PE while showing impaired dilatation responses to ACh compared with control animals (C). While not affecting basal aortic contractility, incubating diabetic aorta for 1 hour with geraniol (R) or 10-gingerol (G) in a concentration range (0.01–1 μM) reduced the exaggerated response to PE. In addition, geraniol or 10-gingerol incubation improved the impaired relaxation response to ACh in a dose dependent manner. Figure. No caption available. Conclusions: In conclusion, both geraniol and 10-gingerol restore normal vascular reactivity in aorta isolated from diabetic rats. Addition of geraniol and 10-gingerol to diabetic therapy may provide superior to alleviate the associated vascular complications.